Translingual Practice on Instagram @folkative Account - Imelda Iza Afkarina; Ribut Wahyudi (Journal of Language and Literature, 2025)
This research is about translingual practice in a digital context (social media), namely the Indonesian infotainment’s Instagram @folkative account. This research is essential because translingual practice increasingly influences social media interaction in this globalized era, enriching cross-cultural expression and creating a digital presence. This qualitative research aims to analyze the pattern(s) of translingual practice and how these patterns are/are applied in the mentioned account. Three theories, Canagarajah’s (2013a) translingual practice theory are used as the core theory, Zappavigna’s (2021) theory of discourse and social media, and Barton’s and Lee’s (2013) theory of computer-mediated communication (CMC) as the supporting theories. The results of this study demonstrate that translingual practice in the @folkative account suggests a complex negotiation process showing the fluidity of languages and the fluidity of interactional modalities. Moreover, digital translingual practice also contains a basic norm of translingual practice: breaking language boundaries, social justice, emotional effect, and social subjectivity. We suggest that future research could broaden the scope of digital platforms to blogs, websites, or online news platforms in order to get a broader and deeper understanding of digital translingual practices.